Overview of Bidirectional DC DC Converter for Energy Storage System in Renewable Energy Power Generation - Tyas Kartika Sari; Dianing Novita Nurmala Putri; Chairul Gagarin Irianto; Maulasukma Widjaja (Program Studi Teknik Elektro Universitas Khairun, 2026)
The integration of renewable energy sources (RES), such as wind and solar energy, has become increasingly growth in power generation systems. However, the intermittent and variable nature of these sources poses challenges, especially in maintaining the stability of the power grid. The address this chalange, energy storage systems (ESS) have emerged as a critical component in renewable energy power generation, enhancing grid stability, improving systems resilience and improving the reliability of the electrical grid. Bidirectional DC-DC converters play a crucial role in integrating RES with the energy storage system and the grid. In this study, a comparative is conducted through literature review, design and calculation of buck-boost bidirectional DC-DC converter for battery charging application in renewable energy power generation. This research paper provides an overview of the various bidirectional DC-DC converter topologies which are suitable for energy storage system applications in renewable energy power generation. The paper dicusses the topologies of bidirectional DC-DC converters, advantages and limitations of different converter topologis including isolated and non-isolated configurations. The result indicate that isolated topologies offer better galvanic isolation and flexibility in voltage conversion, whereas non-isolated converters provide higher efficiency and simpler design, making them more suitable for compact ESS application